The Theoretical-Substantive Characterization of Determining the Business Model of a Bank with the State Participation - Rudevska Viktoriia I. (Bìznes Inform, 2022)
Modern Ukrainian banks with the State participation have different goals and functional purposes in their content, which continue to change in accordance with the transformation of the strategy of management of the banking system’s public sector. However, they play an increased social role, should stimulate the country’s economic growth processes and are now system important banks. In such a situation, the definition of an adequate business model of a bank with the State participation becomes relevant for the research of scholars and the implementation of results in the practical field. Banking institutions are subject to changes in the business model depending on external economic factors, which can be due to both changes in market needs and changes in the competitive environment or normative-legal regulation. This situation in the future can lead not only to changes in the business architecture of the banking sector, but also to impact the pace of economic growth of the country. The article considers modern approaches to the definition and distribution of banks with the State participation according to business models. The study of existing approaches to determining the business models of banks with the State participation in Ukraine allowed to define that the proposed methods are based on the indicators of financial statements of banks and make use of cluster analysis instruments. The proposed author’s improvement of the content of the concepts of «bank with the State participation» and «business model of the bank with the State participation» defined the direction of development of the categorical apparatus, which should specify the object of research, taking into account its functionality and its system and socioeconomic significance for the banking sector and the economy of Ukraine. The article substantiates the author’s view on the classification of banks with the State participation in business models, taking into account the vector of economic growth of the country.